EXTENDED SCATTERING ENVELOPE IN THE Q2237+0305 QUASAR - Berdina, L. A.; Tsvetkova, V. S.; Shulga, V. M. (Видавничий дім «Академперіодика», 2019)
PACS numbers:  94.20.-y, 96.30.YsPurpose: Studying the accretion disc structure in the Q2237+0305 gravitationally lensed quasar in optical wavelengths; estimation of parameters of the matter accretion regime onto a central black hole.Design/methodology/approach: Measuring the time delays between the quasar brightness variations in two spectral ranges allows to obtain direct estimates of distances between the quasar’s zones, which radiate in the selected wavelengths (the reverberation mapping method).Findings: New estimates of the time delays between the Q2237+0305 light curves in the R and V spectral bands have been obtained from the observations of 2004, as well as more accurate estimates for the light curves of the 2005 season reported earlier. The time delay value averaged over the two years is ΔtR-V ≈ 6.7 ± 2.4  days in the observer’s coordinate system, or Δt̃R-V ≈ 2.49 ± 0.9 days in the rest frame. With this delay, a distance between the accretion disk annular zones responsible for the radiation in V and R is  RR-RV = Δt̃R-V · c ≈ 6.46·1015 sm. This indicates an accretion disk size far exceeding that one predicted by the standard thin accretion disc model by Shakura and Sunyaev. In this work, a suggestion is checked that thus large disk size can be a consequence of a super-critical (super-Eddington) accretion regime considered in the classical work by Shakura and Sunyaev, where the supercritical accretion regime has been shown to results in formation of an extended optically thick scattering envelope on the disk periphery.Conclusions: Analytical expressions for the radius and temperature of such an envelope derived by Shakura and Sunyaev have been used in this work to calculate the RR and RV envelope dimensions in the R and V spectral bands expected from the super-critical accretion regime scenario in the Q2237+0305 quasar. The calculations have been made for three values of the black hole mass covering the whole range of the existing estimates for Q2237+0305, from MВH = 2·108 Mʘ to MВH = 20·108 Mʘ. The accretion rate was assumed to be ṁ = 17. The calculated envelope radii in spectral bands R and V are well consistent with the inter-band time delay value of 2.49 days obtained in the present work from the data of observations. Thus, it can be argued that the black hole in the Q2237+0305 quasar is accreting the matter in a moderately super-critical regime, which results in creating an extended optically thick scattering envelope, and this is just in this envelope that the reverberation responses examined in this work arise. Parameter α for the black hole- (efficiency of the angular momentum transport) is varying within 0.005 0.006 minimal mass, and from 0.029 to 0.033 for the maximal one, while parameter A (ratio of the energy losses in Compton scattering to those in free-free transitions) is within 50 to 100.Key words: quasar, black hole, accretion disk, reverberation mappingManuscript submitted 10.07.2019Radio phys. radio astron. 2019, 24(4): 242-253REFERENCES1. SHAKURA, N. I. and SUNYAEV, R. A., 1973. Black holes in binary systems. Observational appearance. Astron. Astrophys. vol. 24, pp. 337–355. DOI: https://doi.org/10.1007/978-94-010-2585-0_132. PRINGLE, J. E. and REES, M. J., 1972. Accretion disc models for compact X-ray sources. Astron. Astrophys. vol. 21, pp. 1–9.3. EIGENBROD, A., COURBIN, F., MEYLAN, G., the EinsteinºAGOL, E., ANGUITA, T., SCHMIDT, R. W. and WAMBSGANSS, J., 2008. Microlensing variability in the gravitationally lensed quasar QSO 2237+0305  Cross. II. Energy profile of the accretion disk. Astron. Astrophys. vol. 490, is. 3, pp. 933–943. DOI: https://doi.org/10.1051/0004-6361:2008107294. ANGUITA, T., SCHMIDT, R. W., TURNER, E. L., WAMBSGANSS, J., WEBSTER, R. L., LOOMIS, K. A., LONG, D. and MCMILLAN, R., 2008. The multiple quasar Q2237+0305 under a microlensing caustic. Astron. Astrophys. vol. 480, pp. 327–334. DOI: https://doi.org/10.1051/0004-6361:200782215. JAROSZYNSKI, M., WAMBSGANSS, J. and PACZYNSKI, B., 1992. Microlensed light curves for thin accretion disks around Schwarzschild and Kerr black holes. Astrophys. J. vol. 396, is. 2, pp. L65–L68. DOI: https://doi.org/10.1086/1865186. WITT, H. J. and MAO, S., 1994. Interpretation of microlensing events in Q2237+0305. Astrophys. J. vol. 429, is. 1, pp. 66–76. DOI: https://doi.org/10.1086/1743027. POOLEY, D., BLACKBURNE, J. A., RAPPAPORT, S. and SCHECHTER, P. L., 2007. X-ray and optical flux ratio anomalies in quadruply lensed quasars. I. Zooming in on quasar emission regions. Astrophys. J. vol. 661, is. 1, pp. 19–29. DOI: https://doi.org/10.1086/5121158. VAKULIK, V. G., SCHILD, R. E., SMIRNOV, G. V., DUDINOV, V. N. and TSVETKOVA, V. S., 2007. Q2237+0305 source structure and dimensions from lightcurve simulation. Mon. Not. R. Astron. Soc. vol. 382, is. 2, pp. 819–825. DOI: https://doi.org/10.1111/j.1365-2966.2007.12422.x9. JIMÉNEZ-VICENTE, J., MEDIAVILLA, E., MUÑOZ, J. A. and KOCHANEK, C. S., 2012 . A robust determination of the size of quasar accretion disks using gravitational microlensing. Astrophys. J. vol. 751, is. 2, id. 106. DOI: https://doi.org/10.1088/0004-637X/751/2/10610. MORGAN, C. W., KOCHANEK, C. S., MORGAN, N. D. and FALCO, E. E., 2010. The Quasar Accretion Disk SizeBlack Hole Mass Relation. Astrophys. J. vol. 712, is. 2, pp. 1129–1136. DOI: https://doi.org/10.1088/0004-637X/712/2/112911. KROLIK, J. H., HORNE, K., KALLMAN, T. R., MALKAN, M. A., EDELSON, R. A. and KRISS, G. A., 1991. Ultraviolet variability of NGC 5548 – Dynamics of the continuum production region and geometry of the broadline region. Astrophys. J. vol. 371, is. 2, pp. 541–562. DOI: https://doi.org/10.1086/16991812. BLANDFORD, R. D. and MCKEE, C. F., 1982. Reverberation mapping of the emission line regions of Seyfert galaxies and quasars. Astrophys. J. vol. 255. pp. 419–439. DOI: https://doi.org/10.1086/15984313. FAUSNAUGH, M. M., STARKEY, D. A., HORNE, K., KOCHANEK, C. S., PETERSON, B. M., BENTZ, M. C., DENNEY, K. D., GRIER, C. J., GRUPE, D., POGGE, R. W., DE ROSA, G., ADAMS, S. M., BARTH, A. J., BEATTY, T. G., BHATTACHARJEE, A., BORMAN, G. A., BOROSON, T. A., BOTTORFF, M. C., BROWN, J. E., BROWN, J. S., BROTHERTON, M. S., COKER, C. T., CRAWFORD, S. M., CROXALL, K. V., EFTEKHARZADEH, S., ERACLEOUS, M., JONER, M. D., HENDERSON, C. B., HOLOIEN, T. W.-S., HUTCHISON, T., KASPI, S., KIM, S., KING, A. L., LI, M., LOCHHAAS, C., MA, Z., MACINNIS, F., MANNE-NICHOLAS, E. R., MASON, M., MONTUORI, C., MOSQUERA, A., MUDD, D., MUSSO, R., NAZAROV, S. V., NGUYEN, M. L., OKHMAT, D. N., ONKEN, C. A., OU-YANG, B., PANCOAST, A., PEI, L., PENNY, M. T., POLESKI, R., RAFTER, S., ROMERO-COLMENERO, E., RUNNOE, J., SAND, D. J., SCHIMOIA, J. S., SERGEEV, S. G., SHAPPEE, B. J., SIMONIAN, G. V., SOMERS, G., SPENCER, M., STEVENS, D. J., TAYAR, J., TREU, T., VALENTI, S., VAN SADERS, J., VILLANUEVA, JR. S., VILLFORTH, C., WEISS, Y., WINKLER, H. and ZHU, W., 2018. Continuum Reverberation Mapping of the Accretion Disks in Two Seyfert 1 Galaxies. Astrophys. J. vol. 854, is. 2, id. 107. DOI: https://doi.org/10.3847/1538-4357/aaaa2b14. GRIER, C. and SDSS-RM COLLABORATION, 2017. The Sloan Digital Sky Survey Reverberation Mapping Project: Quasar Reverberation Mapping Studies. American Astronomical Society Meeting. vol. 229, id. 414.0115. BERDINA, L. A., TSVETKOVA, V. S. and SHULGA, V. M., 2018. Reverberation Responses in Light Curves of the Q2237+0305 Quasar. Radio Phys. Radio Astron. vol. 23, is. 4, pp. 235–243. (in Russian). DOI: https://doi.org/10.15407/rpra23.04.23516. DUDINOV, V. N., SMIRNOV, G. V., VAKULIK, V. G., SERGEEV, A. V. and KOCHETOV, A. E., 2010. Gravitational Lensed System Q2237-0305 in 2001–2008: Observations at the Maidanak Mountain. Radio Phys. Radio Astron. vol. 15, is. 4, pp. 387–398. (in Russian). DOI: https://doi.org/10.1615/RadioPhysicsRadioAstronomy.v2.i2.4017. POINDEXTER, S. and KOCHANEK, C. S., 2010. Microlensing Evidence that a Type 1 Quasar is Viewed Face-On. Astrophys. J. vol. 712, is. 1, pp. 668–673. DOI: https://doi.org/10.1088/0004-637X/712/1/66818. FRANK, J., KING, A. and RAINE, D. J., 2002. Accretion Power in Astrophysics. Third Edition. Cambridge: Cambridge University Press. DOI: https://doi.org/10.1017/CBO978113916424519. AGOL, E., JONES, B. and BLAES, O., 2000. Keck midinfrared imaging of QSO 2237+0305. Astrophys. J. vol. 545, is. 2, pp. 657–663. DOI: https://doi.org/10.1086/31784720. KOCHANEK, C. S., 2004. Quantitative interpretation of quasar microlensing light curves. Astrophys. J. vol. 605, is. 1, pp. 58–77. DOI: https://doi.org/10.1086/38218021. YEE, H. K. C. and DE ROBERTIS, M. M., 1991. Spatially resolved spectroscopy of Lyman-alpha and CIV in the gravitational lens 2237+030. Astrophys. J. vol. 381, is. 2, pp. 386–392. DOI: https://doi.org/10.1086/17066122. SLUSE, D., SCHMIDT, R., COURBIN, F., HUTSEMÉKERS, D., MEYLAN, G., EIGENBROD, A., ANGUITA, T., AGOL, E. and WAMBSGANSS, J., 2011. Zooming into the broad line region of the gravitationally lensed quasar  the Einstein Cross. III. Determination QSO 2237+0305  of the size and structure of the CIV and CIII] emitting regions using microlensing. Astron. Astrophys. vol. 528, id. 100. DOI: https://doi.org/10.1051/0004-6361/20101611023. ASSEF, R. J., DENNEY, K. D., KOCHANEK, C. S., PETERSON, B. M., KOZŁOWSKI,  S., AGEORGES, N., BARROWS, R. S, BUSCHKAMP, P., DIETRICH, M., FALCO, E., FEIZ, C., GEMPERLEIN, H., GERMEROTH, A., GRIER, C. J., HOFMANN, R., JUETTE, M., KHAN, R., KILIC, M., KNIERIM, V., LAUN, W., LEDERER, R., LEHMITZ, M., LENZEN, R., MALL, U., MADSEN, K. K., MANDEL, H., MARTINI, P., MATHUR, S., MOGREN, K., MUELLER, P., NARANJO, V., PASQUALI, A., POLSTERER, K., POGGE, R. W., QUIRRENBACH, A., SEIFERT, W., STERN, D., SHAPPEE, B., STORZ, C., VAN SADERS, J., WEISER, P. and ZHANG, D., 2011. Black hole mass estimates based on CIV are consistent with those based on the Balmer lines. Astrophys. J. vol. 742, is. 2, id. 93. DOI: https://doi.org/10.1088/0004-637X/742/2/9324. EIGENBROD, A., COURBIN, F., SLUSE, D., MEYLAN, G. and AGOL, E., 2008. Microlensing variability in  the the gravitationally lensed quasar QSO 2237+0305  Einstein Cross . I. Spectrophotometric monitoring with the VLT. Astron. Astrophys. vol. 480, is. 3, pp. 647–661. DOI: https://doi.org/10.1051/0004-6361:2007870325. MEDIAVILLA, E., JIMÉNEZ-VICENTE, J., MUÑOZ, J. A. and MEDIAVILLA, T., 2015. Resolving the innermost region of the accretion disk of the lensed quasar Q2237+0305 through gravitational microlensing. Astrophys. J. Lett. vol. 814, is. 2, id. L26. DOI: https://doi.org/10.1088/2041-8205/814/2/L2626. FAUSNAUGH, M. M., DENNEY, K. D., BARTH, A. J., BENTZ, M. C., BOTTORFF, M. C., CARINI, M. T., CROXALL, K. V., DE ROSA, G., GOAD, M. R., HORNE, K., JONER, M. D., KASPI, S., KIM, M., KLIMANOV, S. A., KOCHANEK, C. S., LEONARD, D. C., NETZER, H., PETERSON, B. M., SCHNÜLLE, K., SERGEEV, S. G., VESTERGAARD, M., ZHENG, W.-K., ZU, Y., ANDERSON, M. D., ARÉVAL, P., BAZHAW, C., BORMAN, G. A., BOROSON, T. A., BRANDT, W. N., BREEVELD, A. A., BREWER, B. J., CACKETT, E. M., CRENSHAW, D. M., DALLA BONTÀ, E., DE LORENZO-CÁCERES, A., DIETRICH, M., EDELSON, R., EFIMOVA, N. V., ELY, J., EVANS, P. A., FILIPPENKO, A. V., FLATLAND, K., GEHRELS, N., GEIER, S., GELBORD, J. M., GONZALEZ, L., GORJIAN, V., GRIER, C. J., GRUPE, D., HALL, P. B., HICKS, S., HORENSTEIN, D., HUTCHISON, T., IM, M., JENSEN, J. J., JONES, J., KAASTRA, J., KELLY, B. C., KENNEA, J. A., KIM, S. C., KORISTA, K. T., KRISS, G. A., LEE, J. C., LIRA, P., MACINNIS, F., MANNE-NICHOLAS, E. R., MATHUR, S., MCHARDY, I. M., MONTOURI, C., MUSSO, R., NAZAROV, S. V., NORRIS, R. P., NOUSEK, J. A., OKHMAT, D. N., PANCOAST, A., PAPADAKIS, I., PARKS, J. R., PEI, L., POGGE, R. W., POTT, J.-U., RAFTER, S. E., RIX, H.-W., SAYLOR, D. A., SCHIMOIA, J. S., SIEGEL, M., SPENCER, M., STARKEY, D., SUNG, H.-I., TEEMS, K. G., TREU, T., TURNER, C. S., UTTLEY, P., VILLFORTH, C., WEISS, Y., WOO, J.-H., YAN, H. and YOUNG, S., 2016. Space Telescope and Optical Reverberation Mapping Project. III. Optical Continuum Emission and Broadband Time Delays in NGC 5548. Astrophys. J. vol. 821, is. 1, id. 56. DOI: https://doi.org/10.3847/0004-637X/821/1/5627. AGOL, E. and KROLIK, J. H., 2000. Magnetic Stress at the Marginally Stable Orbit: Altered Disk Structure, Radiation, and Black Hole Spin Evolution. Astrophys. J. vol. 528, is. 1, pp. 161–170. DOI: https://doi.org/10.1086/30817728. GASKELL, C. M., GOOSMANN, R. W. and KLIMEK, E. S., 2008. Structure and kinematics of the broadline region and torus of Active Galactic Nuclei. Mem. S. A. It. vol. 79, pp. 1090–1095.29. BEGELMAN, M. C., 1978. Black holes in radiation-dominated gas: an analogue of the Bondi accretion problem. Mon. Not. R. Astron. Soc. vol. 184, is. 1, pp. 53–67. DOI: https://doi.org/10.1093/mnras/184.1.5330. ABRAMOWICZ, M. A., CZERNY, B., LASOTA, J. P. and SZUSZKIEWICZ, E., 1988. Slim accretion disks. Astrophys. J. vol. 332, pp. 646–658. DOI: https://doi.org/10.1086/16668331. NARAYAN, R. and YI, I., 1994. Advection-dominated accretion: a self-similar solution. Astrophys. J. vol. 428, is. 1, pp. L13–L16. DOI: https://doi.org/10.1086/18738132. EGGUM, G. E., CORONITI, F. V. and KATZ, J. I., 1988. Radiation hydrodynamic calculation of super-Eddington accretion disks. Astrophys. J. vol. 330, is. 1, pp. 142–167. DOI: https://doi.org/10.1086/16646233. OHSUGA, K., MINESHIGE, S., MORI, M. and UMEMURA, M., 2002. Does the slim-disk model correctly consider photon-trapping effects? Astrophys. J. vol. 574, is. 1, pp. 315–324. DOI: https://doi.org/10.1086/34079834. OHSUGA, K., MORI, M., NAKAMOTO, T. and MINESHIGE, S., 2005. Supercritical accretion flows around black holes: two-dimensional, radiation pressure-dominated disks with photon trapping. Astrophys. J. vol. 628, pp. 368–381. DOI: https://doi.org/10.1086/43072835. OKUDA, T., TERESI, V., TOSCANO, E. and MOLTENI, D., 2005. Black hole accretion discs and jets at superEddington luminosity. Mon. Not. R. Astron. Soc. vol. 357, is. 1, pp. 295–303. DOI: https://doi.org/10.1111/j.1365-2966.2005.08647.x36. ABOLMASOV, P. and SHAKURA, N. I., 2012. Microlensing evidence for super-Eddington disc accretion in quasars. Mon. Not. R. Astron. Soc. vol. 427, is. 3, pp. 1867–1876. DOI: https://doi.org/10.1111/j.1365-2966.2012.21881.x37. OHSUGA, K. and MINESHIGE, S., 2011. Global Structure of Three Distinct Accretion Flows and Outflows around Black Holes from Two-dimensional Radiation-magnetohydrodynamic Simulations. Astrophys. J. vol. 736, is. 1, id. 2. DOI: https://doi.org/10.1088/0004-637X/736/1/2